1968
DOI: 10.1017/s0022172400028382
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of Q fever in Staffordshire

Abstract: This article describes an outbreak of Q fever involving 24 men (five prison officers and nineteen detainees) in one of H.M. Detention Centres. The evidence collected points strongly to the consumption of raw milk as the route of infection. This appears to be the first milk-borne outbreak of Q fever to be reported in Britain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1970
1970
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…However, suspected milk-borne outbreaks are rare in the UK. Unpasteurised cow's milk purchased by a patient was thought to be responsible for an outbreak of Q fever in a hospital in London in 1950 (Marmion and Harvey 1956) and it was concluded that raw milk was responsible for an outbreak of Q fever in a boys' detention centre in Staffordshire in April 1967 (Brown et al 1968). Although these studies are highly suggestive of the consumption of unpasteurised milk being the source of the outbreak, there is still uncertainty associated with this link (EFSA 2010).…”
Section: Consumption Of Unpasteurised Milk and Milk Productsmentioning
confidence: 99%
“…However, suspected milk-borne outbreaks are rare in the UK. Unpasteurised cow's milk purchased by a patient was thought to be responsible for an outbreak of Q fever in a hospital in London in 1950 (Marmion and Harvey 1956) and it was concluded that raw milk was responsible for an outbreak of Q fever in a boys' detention centre in Staffordshire in April 1967 (Brown et al 1968). Although these studies are highly suggestive of the consumption of unpasteurised milk being the source of the outbreak, there is still uncertainty associated with this link (EFSA 2010).…”
Section: Consumption Of Unpasteurised Milk and Milk Productsmentioning
confidence: 99%
“…7 % among non-exposed people. Other authors used the same argument on the basis of observations in England [4,17,56] and in other countries [18,19,25,[57][58][59][60]. Nevertheless several reports mentioned the oral route as possible but infrequent, circumstantial, or needing a very high dose [15,33,44,[61][62][63].…”
Section: Transmission Of Q Fever To Peoplementioning
confidence: 99%
“…The significance of infection acquired via the oral route remains a subject of discussion (Lorenz et al, 1998) and the role of drinking unpasteurized milk in C. burnetii infection remains controversial. Epidemiologic studies suggest that the consumption of contaminated unpasteurized milk has been a mode of exposure to C burnetii for humans (Christie, 1980;Fishbein and Raoult, 1992;Benson et al, 1963;Brown et al, 1968;Connolly et al 1990;Hatchette et al, 2001). Benson et al, (1963) reported that 42 of 120 persons who were routinely drinking unpasteurized milk tested positive for C. burnetii in at least one immunological test during the reference period.…”
Section: Milk and Dairy Products As A Source Of C Burnetii For The Cmentioning
confidence: 99%